Investigation of flow pattern in upper human airway including oral and nasal inhalation by PIV and CFD - Phuong, Nguyen Lu; Ito, Kazuhide (Building and environment, 2015)
Breathing is one of the most essential processes in the human body. The basic functions of breathing are to exchange gases (supplying oxygen from ambient air and removing carbon dioxide from the blood) and also to exchange heat and moisture through mucous surfaces of the airway. During an average lifetime, human beings experience significant exposure to indoor air and countless of contaminants/particles via inhalation. In this study, experimental and numerical results of flow fields in a realistic respiratory model were obtained. Flow patterns in a realistic replica model of the human respiratory tract were investigated with particle image velocimetry (PIV) under three constant breathing conditions; 7.5, 15 and 30 L/min. Computational fluid dynamics (CFD) analyses were conducted on turbulent models with boundary conditions corresponding to the experimental models. We used four RANS turbulence models to predict airflow in a realistic human airway model: two low Reynolds (Re) number-type k–ε turbulence models, RNG k–ε model, and the SST k–ω model. The CFD results were compared with PIV data and showed relatively good agreement in trachea region in all cases. •An idealized- and realistic-human airway model were main subjects in this study.•We conducted CFD and PIV to investigate the flow pattern in both models.•Inhalation mode were applied in oral and nasal cavity to examine the effect of inlet conditions.•The prediction and actual result of a flow field shown a good agreement.